Why I'm afraid of bees - Stine, R. L. (New York : Scholastic, 1994)
Gary's dream is about to come true. He's going to exchange bodies with another kid for a whole week but the new body isn't human.
"An Apple paperback."
"RL: 4"--P. [4] of cover.
"008-012"--P. [4] of cover.
570
570
Accelerated Reader AR
Keywords: Horror tales; Bees -- Juvenile fiction